New Developments and Opportunities of Microbiota in Treating Breast Cancers - Meng, Zihui; Ye, Zixuan; Zhu, Pengrong; Zhu, Jianguo; Fang, Shuguang; Qiu, Tianzhu; Li, Yanan; Meng, Lijuan (Frontiers in Microbiology, 2022)
Despite the prevalence of breast cancer (BC), over half of BC cases are unrelated to known risk factors, which highlights the importance of uncovering more cancer-related factors. Currently, the microbiota has been proven to be a potent modulator of the tumor environment in BC, which regulates the immune balance in tumor-related networks. Through a large amount of data accumulation, the microbiota has shown many possibilities to reveal more insights into the development or control of BC. To expand the potential benefits of patients with BC, this study discusses the distribution profile and the effect mechanism of BC-related microbiota on tumors and further discusses its impact on different tumor therapies. Finally, we summarize the possibility of targeting microbiological therapies to improve BC treatment or in combination with other therapies.